Implementation of The Role of The North Sumatra Regional Office of The Ministry of Law and Human Rights in The Formation of Regional Regulations on The Spatial Plan of Gunung Sitoli City, Indonesia - Manullang, Rio Saputra; Simamora, Janpatar (Manunggal Halim Jaya, 2025)
Harmonizing regional regulations is important to ensure that local regulations do not conflict with national policies and regulations. The focus of this research is the role of the North Sumatra Regional Office of the Ministry of Law and Human Rights in harmonizing Gunung Sitoli City Regional Regulation Number 12 of 2012 concerning the Regional Spatial Plan (RTRW). This research investigates documents through a descriptive qualitative approach to provide an in-depth overview of the harmonization process, the challenges faced, and the impact of policy implementation. The research results show that the North Sumatra Regional Office of the Ministry of Law and Human Rights is key in aligning regional spatial planning regulations (Perda RTRW) with national regulations. The harmonization process involves a review of substance and technical aspects, the preparation of recommendations, and coordination between local governments and related agencies. However, the research also identified various constraints, such as limited resources and differences in technical interpretation, that affect the effectiveness of harmonization. The effectiveness evaluation shows that the harmonization process successfully improved the alignment of RTRW regional regulations with national policies, although some minor adjustments are needed. The positive impact of this harmonization includes improved coordination between government agencies and a more substantial legal basis for implementing RTRW. The recommendations from this study include improvements in the harmonization process and policy adjustments to address the identified implementation challenges. This research is expected to enhance the understanding of regulatory harmonization mechanisms and improve the effectiveness of spatial planning policies in Gunung Sitoli City through the strategic role of the Regional Office of the Ministry of Law and Human Rights.